(untitled) - Lavenda, Robert H.; Robert Lavenda; Emily Schultz (Boston)
This concise and affordable introduction to the basic ideas and practices of contemporary cultural anthropology addresses the needs of anthropology professors who make extensive use of ethnographies and other supplementary readings in their courses. Core Concepts in Cultural Anthropology offers a thorough annotated bibliography of the terms and concepts that anthropologists use in their work, while its conceptual and theoretical framework prepares students to read ethnography more effectively
Includes bibliographical references (p. 239-249) and index
Keywords: Ethnology; Ethnology